Steady-state and dynamic validation of a parabolic trough collector model using the ThermoCycle Modelica library. (1st November 2018) - Desideri, Adriano; Dickes, Rémi; Bonilla, Javier; Valenzuela, Loreto; Quoilin, Sylvain; Lemort, Vincent
Highlights: A dynamic model for the modelling of parabolic through collectors is proposed. A steady-state and dynamic validation against data from the PSA facility is presented. Simulation results shown good accuracy with experimental data. A discretization level of 20 CV is found to be optimal between model accuracy and simulation speed. A 1 CV collector model is proposed for daily or longer time frame. Abstract: Small-capacity (<200 kWel ) concentrated solar power plants has been recognized as a promising technology for micro power applications. In particular, parabolic trough collectors have been identified as the most promising focusing technology. In this context, physics-based dynamic model of parabolic trough constitutes a significant tool for the further development of the technology, allowing to evaluate and optimize response times during transients, or to implement and test innovative control strategies. In this contribution, the dynamic model of a parabolic trough line based on the ThermoCycle Modelica library is validated against steady-state and transient experimental results from the parabolic trough test loop available at the Plataforma Solar de Almería, Spain. The simulation results are in good agreement with the measurements, both in steady-state and in transient conditions. The validated model is readily usable to investigate demanding dynamics-based problems for low capacity solar power systems.